Duration of exposure to epidural anesthesia at delivery, DNA methylation in umbilical cord blood and their association with offspring asthma in Non-Hispanic Black women. Issue 1 (13th December 2022) - Wang, Yaxu; Tzeng, Jung-Ying; Huang, Yueyang; Maguire, Rachel; Hoyo, Cathrine; Allen, Terrence K
Abstract: Epidural anesthesia is an effective pain relief modality, widely used for labor analgesia. Childhood asthma is one of the commonest chronic medical illnesses in the USA which places a significant burden on the health-care system. We recently demonstrated a negative association between the duration of epidural anesthesia and the development of childhood asthma; however, the underlying molecular mechanisms still remain unclear. In this study of 127 mother–child pairs comprised of 75 Non-Hispanic Black (NHB) and 52 Non-Hispanic White (NHW) from the Newborn Epigenetic Study, we tested the hypothesis that umbilical cord blood DNA methylation mediates the association between the duration of exposure to epidural anesthesia at delivery and the development of childhood asthma and whether this differed by race/ethnicity. In the mother–child pairs of NHB ancestry, the duration of exposure to epidural anesthesia was associated with a marginally lower risk of asthma (odds ratio = 0.88, 95% confidence interval = 0.76–1.01) for each 1-h increase in exposure to epidural anesthesia. Of the 20 CpGs in the NHB population showing the strongest mediation effect, 50% demonstrated an average mediation proportion of 52%, with directional consistency of direct and indirect effects. These top 20 CpGs mapped to 21 genes enriched for pathways engaged in antigen processing, antigen presentation, protein ubiquitination and regulatory networks related to the Major Histocompatibility Complex (MHC) class I complex and Nuclear Factor Kappa-B ( NFkB ) complex. Our findings suggest that DNA methylation in immune-related pathways contributes to the effects of the duration of exposure to epidural anesthesia on childhood asthma risk in NHB offspring.